Effect of different electrostimulation currents on female urinary incontinence: A protocol of a randomized controlled trial - Avramidis, Raissa Escandiusi [UNESP]; Barbosa, Angélica Mércia Pascon [UNESP]; de Aquino Nava, Guilherme Thomaz [UNESP]; Nagami, Danielle Hikaru [UNESP]; Prudencio, Caroline Baldini [UNESP]; Pedroni, Cristiane Rodrigues [UNESP] (Public Library of Science (PLoS), 2022)
Introduction Urgency urinary incontinence (UUI) is characterized by involuntary urine leakage immediately after reporting of sudden, compelling desire to void. Electrostimulation and non-invasive neuromodulation have been considered as the first and third line of UUI treatment but there is a lack of consensus on which parameters are more efficient. Thus, this study aims to compare the effect of low versus medium frequency currents on urinary incontinence severity and quality of life in women with UUI complains. Methods It will be a randomized controlled trial with 5 arms, double-blinded (outcome assessor and statistician). The study was approved by the Research Ethics Committee (CAAE: 11479119.9.0000.5406) and has been prospectively registered on the Brazilian Registry of Clinical Trials (RBR-8bkkp6). Concerning, double-blind process, the blinded assessor will be responsible for evaluate primary and secondary outcomes at baseline and follow-up without information about allocation and the statistician will perform analyses without information about group codification. One hundred and five participants will be randomized to receive: (1) Transcutaneous tibial nerve stimulation-low frequency, (2) Transcutaneous tibial nerve stimulation-high frequency, (3) Aussie median frequency, (4) Interferencial median frequency or (5) High voltage stimulation. The application will be performed during 20 sessions of 45-minutes, twice a week for 10 weeks, in groups of maximum 5 participants. The participants will be evaluated before treatment (baseline- 0 week), during the treatment (5 weeks) and after the last treatment session (10 weeks). The primary outcomes measures will be UI severity and quality of life, and the secondary outcome will be pelvic floor strength. Statistical analysis will be performed using SPSS software version 24.0 for Windows (IBM Corp., Armonk, N.Y., USA). The variables will be described by the mean and 95% confidence interval. The distribution of normality will be analyzed by the Shapiro-Wilk test. ANOVA for repeated measures will be performed. Mauchly’s test the hypothesis of sphericity and when if this violated the hypotheses, the analyses will be based on the Greenhouse-Geisser test. Peer-to-peer comparisons will be performed using the Bonferroni Post-Hoc test. The significant level adopted will be 5% (p ≤ 0.05). Conclusion This study will enhance knowledge about effect of different neuromodulation currents in the improvement of UUI.